Enhanced utilization of biotechnology research and development innovations in Eastern and Central Africa for agroecological intensification - Masiga, C.W.; Mugoya, C.; Ali, R.; Mohamed, A.; Osama, S.; Ngugi, A.; Kiambi, D.; Villiers, S. de; Ngugi, K.; Niyibigira, T.; Tesfamichel, A.; Machuka, J.; et al. (Springer, 2014)
The Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA) through its Agrobiodiversity and Biotechnology Programme is enhancing the utilization of biotechnology research and development innovations in Eastern and Central Africa (ECA). We present successes in the application of biotechnology to enhance the productivity of cassava, sweet potato, banana, maize and sorghum in ECA. These products—drought tolerant maize, sorghum resistant to striga, as well as the technology for producing and distributing disease free planting materials of cassava, sweet potato and banana to farmers—are central for the agro-ecological intensification of farming systems in the central African highlands.